Perkembangan Filsafat dan Sains Pada Zaman Renaissance dan Zaman Modern - Alif Mardiana; Silvia Qaulina Damayanti; I Ketut Mahardika; Suratno Suratno (Jurnal Ilmiah Wahana Pendidikan, 2023)
In seeking the truth, humans use philosophy and science. Philosophy and Science (science) are interrelated. In fact, there are several sciences that do not use philosophy in developing science. Therefore philosophy plays a very important role in the development of science. Philosophy continues to develop, the development of this philosophical thought began in the ancient Greek era to contemporary times. The four periodizations include ancient times, medieval times, modern times, and present times. The emergence of the Renaissance is the beginning of the modern century. Many figures contributed to the Renaissance which continued in modern times. The purpose of this research is to describe the development of philosophy and science in the Renaissance and modern times. The type of research used is library research. The Renaissance era was marked by rapid progress in various fields of science, especially astronomy. There are several famous figures in this era, including Nicholas Copernicus, Johannes Kepler and Galileo Galilei. In modern times it is also continued about the discoveries that have been made in the Renaissance era. Modern science started with Isaac Newton (1643−1727) and Leibniz (1646−1716). There are several streams in the modern century, including rationalism, empiricism, criticism, and positivism